Altered Functions and Interactions of Glaucoma-Associated Mutants of Optineurin - Swarup, Ghanshyam; Sayyad, Zuberwasim (Frontiers in Immunology, 2018)
Optineurin is an adaptor protein that is involved in mediating a variety of cellular processes such as signaling, vesicle trafficking and autophagy. Certain mutations in optineurin (gene OPTN) are associated with primary open angle glaucoma, a leading cause of irreversible blindness, and amyotrophic lateral sclerosis, a fatal motor neuron disease. Glaucoma-associated mutations of OPTN are mostly missense mutations. OPTN mediates its functions by interacting with various proteins andaltered interactions of optineurin mutants with various proteins primarily contribute to functional defects. It interacts with Rab8, myosin VI, Huntigtin, TBC1D17 and transferrin receptor to mediate various membrane vesicle trafficking pathways. It is an autophagy receptor that mediates cargo-selective as well as non-selective autophagy. Glaucoma-associated mutants of OPTN, E50K and M98K, cause defective vesicle trafficking, autophagy and signaling that contribute to death of retinal ganglion cells. Transgenic mice expressing E50K-OPTN show loss of retinal ganglion cells and persistent reactive gliosis. TBK1 protein kinase, which mediates E50K-OPTN and M98K-OPTN induced cell death, is emerging as a potential drug target. Autoimmunity has been implicated in glaucoma but involvement of optineurin or its mutants in autoimmnity has not been explored. In this review, we highlight the main functions of OPTN and how glaucoma-associated mutants alter these functions. We also discuss some of the controversies, such as the role of OPTN in signaling to transcription factor NF-kB, interferon signaling and use of RGC-5 cell line as a cell culture model.